Genes required for specifying cell fates in Drosophila embryonic sensory nervous system. - Jan, Y.N.; Jan, L.Y. (Trends in Neurosciences, 1990)
The nervous system contains a diverse group of cells. Specification of the correct cell fate is obviously important for the proper function of the nervous system, yet how are the fates of different neurons determined during development? Very little is known about the underlying molecular mechanisms used in the mammalian nervous system. How, for example, are certain cells directed to form pyramidal cells rather than local interneurons? In the fruit fly Drosophila melanogaster, and the nematode Caenorhabditis elegans, some progress has been made in studying neuronal fate determination. For instance, in Drosophila, a number of genes acting at different levels have been found to control this process. They function to (1) endow a subset of the ectodermal cells in the early embryo with the potential to become neuronal precursors, (2) commit some of these cells to the fate of neuronal precursors, (3) specify the identity of these neuronal precursors, and (4) specify the identity of the individual progeny cells of a neuronal precursor. In this review, we discuss first the rationale of the genetic approach, then outline the working hypothesis and, finally, briefly describe the genes known to be involved in the formation of the sensory nervous system in Drosophila. We also discuss the prospects for extrapolating these molecular mechanisms and principles to vertebrate and invertebrate neural development.